1989
DOI: 10.1126/science.2472670
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase Amino Acid Sequence: Possible Channel- or Transporter-Like Structure

Abstract: Complementary DNA's that encode an adenylyl cyclase were isolated from a bovine brain library. Most of the deduced amino acid sequence of 1134 residues is divisible into two alternating sets of hydrophobic and hydrophilic domains. Each of the two large hydrophobic domains appears to contain six transmembrane spans. Each of the two large hydrophilic domains contains a sequence that is homologous to a single cytoplasmic domain of several guanylyl cyclases; these sequences may represent nucleotide binding sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
305
0
4

Year Published

1989
1989
1998
1998

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 722 publications
(315 citation statements)
references
References 51 publications
6
305
0
4
Order By: Relevance
“…Figure 2 shows the alignment of C-terminal regions of these ORFs and of the putative catalytic domains of adenylate cyclases. The regions near the C termini of these proteins containing about 180 amino acids showed 27.5 to 55.4% identity to each other, 29.7 to 35.2% identity to the adenylate cyclase of A. cylindrica (26), 25.9 to 31.4% identity to S. platensis CyaA (52), 29.4 to 35.0% identity to R. meliloti Cya1 (4), and 19.2 to 20.9% identity to the C1a region of bovine type I adenylate cyclase (28). We concluded that these ORFs in p665SK, pQ3SK, pQ2-1SK, p667SK, and pQ6-2SK are the adenylate cyclase genes of Anabaena strain PCC 7120 and designated them cyaA, cyaB1, cyaB2, cyaC, and cyaD, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the alignment of C-terminal regions of these ORFs and of the putative catalytic domains of adenylate cyclases. The regions near the C termini of these proteins containing about 180 amino acids showed 27.5 to 55.4% identity to each other, 29.7 to 35.2% identity to the adenylate cyclase of A. cylindrica (26), 25.9 to 31.4% identity to S. platensis CyaA (52), 29.4 to 35.0% identity to R. meliloti Cya1 (4), and 19.2 to 20.9% identity to the C1a region of bovine type I adenylate cyclase (28). We concluded that these ORFs in p665SK, pQ3SK, pQ2-1SK, p667SK, and pQ6-2SK are the adenylate cyclase genes of Anabaena strain PCC 7120 and designated them cyaA, cyaB1, cyaB2, cyaC, and cyaD, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…4.6.1.1) is the enzyme that converts ATP to cAMP. To date, nine distinct isoforms of mammalian AC (designated I to IX) and two splice variants of the type VIII enzyme have been cloned and characterized (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Because of the diversity in their regulation, the various AC isoforms may be broadly divided into five groups.…”
mentioning
confidence: 99%
“…In contrast to receptors and G proteins, the effectors they regulate appear to have little in common. They include enzymes like adenylate cyclase (Krupinski et al, 1989), polyphosphoinositidespecific phospholipase C (Harden, 1989), cyclic GMP phosphodiesterase (Stryer, 1988) and phospholipase A2 (Burch et al, 1986), transporters for Mg2+ (Erdos et al, 1981) and possibly glucose (Kuroda et al, 1987), and ion channels that gate K+ (Yatani et al, 1987a), Ca2+ (Yatani et al, 1987b) or Na+ (Cantiello et al, 1989;Krapivinsky et al, 1989). The molecular details of the interactions between G proteins and effectors are so poorly understood that conserved features of their interactions may not yet have been revealed, but the present evidence suggests that this step in the sequence is probably the least conserved between signalling pathways (see below).…”
Section: Structure and Function In G Protein Signalling Pathwaysmentioning
confidence: 99%